2003
DOI: 10.1590/s0100-204x2003000300005
|View full text |Cite
|
Sign up to set email alerts
|

Potencial discriminatório de três testadores em "topcrosses" de milho

Abstract: Resumo -O objetivo deste trabalho foi determinar o potencial de três testadores endogâmicos elites a fim de avaliar e classificar 15 materiais genéticos para a síntese de híbridos. Quarenta e cinco híbridos mais quatro testemunhas foram avaliados em cinco ambientes, no ano agrícola 2000/2001, utilizando delineamento em blocos ao acaso, com três repetições. Foram avaliados os caracteres peso de grãos corrigido, altura de planta e altura de espiga. As estimativas de capacidade geral e específica de combinação fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(10 reference statements)
0
7
1
1
Order By: Relevance
“…DUARTE et al (2003) found significant difference in the GCA for testers with high values, suggesting that the higher frequency of favorable alleles for improving the GY was in testers than lines. However, if a tester is used only to evaluate the combining abilities of lines, negative GCA estimate for this tester can be more interesting because the better expression of the favorable alleles from different lines depends on the frequency of unfavorable alleles form the testers (BARATA & CARENA, 2006).…”
Section: Resultsmentioning
confidence: 86%
“…DUARTE et al (2003) found significant difference in the GCA for testers with high values, suggesting that the higher frequency of favorable alleles for improving the GY was in testers than lines. However, if a tester is used only to evaluate the combining abilities of lines, negative GCA estimate for this tester can be more interesting because the better expression of the favorable alleles from different lines depends on the frequency of unfavorable alleles form the testers (BARATA & CARENA, 2006).…”
Section: Resultsmentioning
confidence: 86%
“…The SCA values are related with the genetic distance between the tester and the line and show the importance of non-additive interactions, characterized by complementarity in relation to the allele frequency in loci with some dominance among parents (Duarte et al 2003), i.e., SCA is linked to the dominance effects.…”
Section: Use Of Testers For Combining Ability and Selection Of Papapymentioning
confidence: 99%
“…In breeding programs for high performance with great potential, elite lines are used whenever possible. For this reason, in most cases, the testers used are also elite, by which genotypes with market potential can be obtained, besides a prediction of the performance of potential hybrids (Duarte, et al 2003) From a practical point of view, the main purpose of the use of testers is to eliminate lines with unsatisfactory performance from the selection process. In this way, the hybrid development program can be rationalized and becomes more efficient (Elias et al 2000).…”
Section: Use Of Testers For Combining Ability and Selection Of Papapymentioning
confidence: 99%
See 2 more Smart Citations